Two‐year predictors of runaway and homeless episodes following shelter services among substance abusing adolescents. Issue 5 (21st July 2013) - Slesnick, Natasha; Guo, Xiamei; Brakenhoff, Brittany; Feng, Xin
ABSTRACT: Given high levels of health and psychological costs associated with the family disruption of homelessness, identifying predictors of runaway and homeless episodes is an important goal. The current study followed 179 substance abusing, shelter‐recruited adolescents who participated in a randomized clinical trial. Predictors of runaway and homeless episodes were examined over a two year period. Results from the hierarchical linear modeling analysis showed that family cohesion and substance use, but not family conflict or depressive symptoms, delinquency, or school enrollment predicted future runaway and homeless episodes. Findings suggest that increasing family support, care and connection and reducing substance use are important targets of intervention efforts in preventing future runaway and homeless episodes amongst a high risk sample of adolescents.